Phylogenetic relationships and phylogeography of relevant lineages within the complex Campanulaceae family in Macaronesia - Menezes, Tiago (2022)
Macaronesia has long been recognized as a natural model for studying evolutionary processes in plant diversification. Several studies have attempted to focus on single lineages, and few have covered the diversification of a family across all the archipela gos. We used a comprehensive sample to clarify the phylogenetic relationships and the biogeographic history of the Macaronesian Campanulaceae. Hypotheses related to the colonization of these archipelagos will be used to examine the diversification patterns of different lineages. We sequenced the ITS region and six cpDNA markers (atpB, matK, petD, rbcL, trnL-F, and psbA-trnH) from 10 Campanulaceae species, includ ing seven endemic species in Macaronesia. The phylogeny of these taxa was recon structed using maximum parsimony, maximum likelihood, and Bayesian inference. To study the relationships within each lineage, haplotype networks were calculated using NeighborNet and TCS algorithms. Moreover, data were combined with fossil informa tion to construct time-calibrated trees for the Macaronesian Campanulaceae species. The phylogenetic analyses are largely congruent with current taxon circumscriptions, and all the endemic genera formed monophyletic clades, namely Azorina in Azores; Musschia in Madeira; and Campanula in Cape Verde. The Azorina clade and the Cape Verde endemic Campanula may share a common ancestor in North Africa, and the di vergence was dated ca. 12.3 million years ago (Mya). The divergence of the Musschia clade began in the Pliocene ca. 3.4 Mya. Moreover, several examples of intraspecific variation were revealed among the native species with a clear geographic structured patterns, suggesting that cryptic diversity might exist within the native Macaronesian Campanulaceae when compared to the close mainland taxa (e.g., Campanula erinus, Trachelium caeruleum), but additional studies are needed to support the molecular data. This study highlights the power of combining data (e.g., phylogeny and diver gence times, with species distribution data) for testing diversification hypotheses within the unique Macaronesian flora, providing useful information for future conser vation efforts.